1993
DOI: 10.1515/cclm.1993.31.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Enzyme Activities in the Resting Human Polymorphonuclear Leukocyte — Critical Estimate of a Method

Abstract: As a system for study, the isolated human polymorphonuclear leukocyte combines the advantages of a quasi-non-invasive preparation with a nearly complete complement of enzymes of carbohydrate and energy metabolism. However, small sample volumes and, in some cases, very low enzyme activities make high demands on sample processing, storage, and performance of continuous measurements, if the enzyme activities are to be measured with acceptable reproducibility. In the presented study several aspects of homogenizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…For preparation of the sample, ultrasonic disintegrators are successfully used to homogenize cells, after cell culturing or after isolation from the organism. For example, after detailed studies on the usefulness of ultrasonic homogenization on the leukocytes, Fauth et al confirmed that this type of homogenization did not affect enzymatic activity of 13 investigated enzymes [88]. However, the procedure may lead to the disruption of non-covalently bound molecular clusters (like multienzyme complexes) [89].…”
Section: Ultrasonic Homogenizationmentioning
confidence: 99%
“…For preparation of the sample, ultrasonic disintegrators are successfully used to homogenize cells, after cell culturing or after isolation from the organism. For example, after detailed studies on the usefulness of ultrasonic homogenization on the leukocytes, Fauth et al confirmed that this type of homogenization did not affect enzymatic activity of 13 investigated enzymes [88]. However, the procedure may lead to the disruption of non-covalently bound molecular clusters (like multienzyme complexes) [89].…”
Section: Ultrasonic Homogenizationmentioning
confidence: 99%
“…via glycolysis in which one molecule of glucose breaks down into two molecules of pyruvate or reversible transamination reactions, etc. ), but also unites several key metabolic processes (Agam and Gutman 1972; Curi et al 1989, 1988; Fauth et al 1993 and 1990; Frei et al 1975; Fuchs et al 1994; Homem de Bittencourt et al 1993; Ing et al 1997; Newsholme et al 1987; Wu et al 2005 and 2003). …”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotic cells, for example, pyruvate is converted into acetyl-CoA, releasing NADH and carbon dioxide in a process called pyruvate decarboxylation (Fauth et al 1993 and 1990; Fink 2008, 2007a, b, 2004; Willems et al 1978). This oxidative conversion into acetyl-CoA, which is the main input for a series of reactions named after Hans Adolf Krebs (awarded the 1953 Nobel Prize) is usually catalysed by the pyruvate dehydrogenase complex as part of aerobic respiration (Krebs 1940; 1938).…”
Section: Introductionmentioning
confidence: 99%
“…And in fact, the energy output is high, because the transition of one molecule of pyruvate via the TCA cycle, together with oxidative phosphorylation, produces 15 molecules of ATP as well as NADPH, which can for example be further metabolized by membranous NADPH oxidase (nicotinamide adenine dinucleotide phosphate-oxidase) as well [9] [10] [42]- [44]. Under physiological conditions, the complex is inactive and only activated during respiratory burst.…”
Section: Pyruvate Induced Effects: Is There An Impact By Adding a Glumentioning
confidence: 99%